Whey Protein Isolate-Based Edible Coatings Incorporated with Jojoba Oil as a Novel Approach for Improving the Quality of Fresh-Cut Root Parsley during Refrigerated Storage - Sabina Galus; Magdalena Mikus; Agnieszka Ciurzyńska; Monika Janowicz (Applied Sciences, 2022)
In this paper, the effect of whey-protein-isolate-based edible coatings with the addition of jojoba oil at concentrations of 1 and 2% on the qualitative characteristics of fresh-cut root parsley was evaluated. Changes in hardness, color parameters, and the contents of polyphenols and flavonoids over 28 days of refrigerated storage, as well as changes in structure, were examined. It was observed that fresh-cut parsley, uncoated and coated with a protein solution, was characterized by a decrease in hardness, from 59.32 and 59.88 to 50.98 and 48.33 N, respectively, while parsley coated with whey protein isolate with the addition of jojoba oil showed an increase in hardness during storage, from 56.28 to 66.23 N and from 52.17 to 60.49 for 1% and 2% of jojoba-oil-containing formulations, respectively. The L*, a*, and b* color parameters and hue angle mostly remained at similar levels, which indicate the maintenance of the desired color, but changes in the values were observed during storage. Parameter L* was between 79.56 and 85.33 in the control samples and between 72.54 and 84.19 in the coated samples. It was shown that the use of whey protein coatings and storage time had a positive impact on the contents of polyphenols and flavonoids in the fresh-cut parsley. The highest changes in polyphenols, from 3.13 to 9.82 mg GAE/g d.m., were observed for the samples coated with the formulation containing 1% of jojoba oil. The highest increase in flavonoid content, from 23.65 to 40.60 mg QE/g d.m., was observed for the samples coated with the film-forming solution with 2% of jojoba oil. Scanning electron microscopy showed a smaller number of pores in the vegetable tissue as a result of the coatings, and this was the most noticeable for the samples without the jojoba oil. Storage deteriorated the quality of the fresh-cut parsley surface, and the drying effect was visible. The use of protein coatings incorporated with jojoba oil modifies the quality characteristics of fresh-cut parsley, and this can find application in reducing the waste of minimally processed vegetables during storage.